Virtual Reality in Education: Transforming Learning through Immersive Technology - Analyti, Efi; Charitou, Roumpini; Pesmatzoglou, Evanthia; Stavrogiannopoulou, Maria; Schoina, Ioanna; Travlou, Chrysi; Mitroyanni, Evangelia (Technium Education and Humanities, 2024)
This paper explores the integration of virtual reality (VR) in educational settings, emphasizing its potential to revolutionize traditional learning methods. VR provides immersive and interactive environments that engage students more deeply with the material, leading to improved retention and understanding of complex concepts. By simulating real-world scenarios and offering hands-on experiences in subjects like science, history, language learning, and vocational training, VR allows students to visualize and explore content in ways that traditional methods cannot. The paper also discusses the key benefits of VR, such as increased student engagement, enhanced experiential learning, and opportunities for practical, risk-free simulations. Additionally, it highlights the challenges and barriers to its widespread adoption, including the high cost of hardware and software, technological limitations, and the need for comprehensive teacher training. Furthermore, the potential of combining VR with artificial intelligence (AI) to create personalized learning experiences is explored as a future development. In conclusion, while VR presents certain challenges, its transformative potential in education is undeniable. As the technology advances and becomes more affordable, VR is likely to play an increasingly important role in shaping the future of education, making learning more engaging, interactive, and tailored to individual student needs.